Capital Flows and The Macro Economy: The Indian Experience - Seth, A. K.; Varma, Sumati (Journal of Nepalese Business Studies, 2008)
This paper examines the macro-economic impact of capital flows into India. The variables identified in the study have been drawn on the basis of the transmission mechanism – to see how capital flows are transmitted into the economic system. To examine the issue the paper uses simple regression and Granger’s Error Correction technique, which analyses long run and short run impact together. It has been found that out of the macro variables selected almost all are influenced by capital flows and represent the monetary environment of the economy.The Journal of Nepalese Business Studies Vol. IV, No. 1(2007) pp. 62-74